(untitled) - Nguyen, Thanh Tong (Can Tho, 2010)
This research paper examines the effects of borrowed words from English on French teaching in Vietnam. The data analysis shows that the teaching and learning French today have a lot of difficulties.
Keywords: French language,Tiếng Pháp,Vietnamese language,Tiếng Việt; Study and teaching,Vietnamese speakers,Dạy và học,Người nói tiếng Việt,Grammar, Comparative,Ngữ pháp, So sánh; French,Tiếng Pháp